PENGARUH PENGGUNAAN MEDIA AUDIO DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VSDN 001 RUMBAI KOTA PEKANBARU - Asmardi ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aims to reveal the influence of the use of Media Audio and Motivation Learning students to the Indonesian student learning outcomes through four formulation of the problem: (1) whether there is any influence student learning outcomes using audio media than the conventional way students learn?, (2) whether the student that have a high motivation using audio media to obtain higher learning outcomes than students to have high motivation to study by conventional means?, (3) whether students who have low motivation to learn by using audio media to obtain higher learning outcomes than students have low motivation to learn with the conventional way?, and (4) whether there is interaction between the use of audio media and students' motivation towards learning Indonesian? This research is a quasi experimental by treatment block. This research was conducted at SDN 001 Rumbai Pekanbaru semester odd years 2010/2011. Samples were taken with Porposive random sampling technique. Data were collected through the initial test and final test. Data were analyzed using t test and analysis of variance.The results of data analysis showed that: Students who studied on the basis of audio media to obtain higher learning outcomes than students who learn by conventional means. Students who have high motivation to learn with audio media to obtain higher learning outcomes than students who have high motivation to study by conventional means. Students who have low motivation to learn based on audio media to obtain higher learning outcomes than students who have low motivation to study by conventional means. There was no interaction between the audio media and students' motivation. It can be concluded that the audio media significantly influence student learning outcomes.